The right to information in the TRNC: Problems and solutions - Azer, Can (My University, 2013)
The right to information, which is not only a direct means of participating in government, but also is an essential element for democratic and transparent administration, have been recognized by many countries in the last fifteen years. This right was adopted by Turkish Republic of North Cyprus with Statute on Right to Information No: 12/2006. The legal developments in Turkey and Europe have directly affected the TRNC in general. After the Republic of Turkey enacted the legislation on the right to information following the Annan referendum, the TRNC has launched the process for the alignment of its laws to the EU laws. 12/2006 is one of the outcomes of this process. This study examines pros and cons of the relevant Act, and endeavors to bring some suggestions.
KKTC'de Bilgi Edinme Hakki, Sorunlari ve Çozum Onerileri
Keywords: Freedom of information; Turkis republic of north cyprus